Duties and Authority of The Regional Representative Council in Preparing Regional Revenue and Expenditure Budget - Lutfi Roid Mahendra; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2023)
This study aims to find out and analyze the legal rules regarding the preparation of the APBD in Indonesian laws and regulations, the preparation of the state financial budget according to an Islamic perspective and the function of the DPRD's budget in regional development. The approach method used in this research is normative juridical method. This research is a type of descriptive research. The form and type of data used are primary legal materials in the form of laws, documents, journals and books as well as secondary legal materials, namely DPRD documents obtained regarding the preparation of the APBD. In this study, data were collected using the literature study method. Once collected, the data will be processed and discussed using qualitative normative methods. The preparation of the Regional Revenue and Expenditure Budget (APBD) is regulated in Law Number 23 of 2014 concerning Regional Government. The preparation of the state financial budget according to Islamic law is based on the principles of Islamic economics which includes concepts such as maqasid al‐shariah and muamalah. DPRD has an important role in the regional development budget. The DPRD functions as a supervisor for the implementation of regional development as well as the discussion and approval of the APBD.